Begining and precodintions of secret Molotov Ribbentropp pacts (1922–1932) - Kasparavičius, Algimantas (Genocidas ir rezistencija, 2000)
The task of this presentation is essentially threefold: 1) to answer the question of when, where and why the idea and considerations to make the eastern Baltic region the object of an international political bargain during the inter–war period, and to trace the development of these considerations; 2) to find out whether the Baltic states and Poland themselves, by their foreign policy, did not fuel the above tendencies and did not contribute to the situation into which they found themselves on the eve of the Second World War; 3) to determine the means applied by the Soviet Union (Russia) to expand its political influence in the Baltic states while making arrangements for their ultimate annexation.
Keywords: Soviet Union; Germany; Molotov-Ribbentropp pact; Baltic countries; interwar period